2012
DOI: 10.1002/j.1875-9114.2012.01091.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Changes in Inhaled Corticosteroid Use and Markers of Uncontrolled Asthma During Pregnancy

Abstract: Because of residual confounding by asthma severity, our study was not able to show that women who stopped inhaled corticosteroids during pregnancy were at increased risk of having an asthma exacerbation. However, women who stopped corticosteroids tended to have a milder form of asthma, which is reassuring and suggests that women can recognize, to a certain extent, the need to continue taking their controller agents if necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 34 publications
2
14
0
Order By: Relevance
“…Severe asthma increases the requirement for ICS treatment and asthma severity increases the risk of an exacerbation. In our cohort, women with recurrent loss of control are probably similar to findings from previous studies [25] in that ICS use is a reflection of asthma severity, and therefore, they are more susceptible to worsening disease in pregnancy especially if there is a lack of compliance with medication. Previous work has demonstrated that cigarette use in pregnancy is associated with worsening asthma and an increased incidence of exacerbations [15], which may also apply to an increased risk of loss of control as demonstrated in this study.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Severe asthma increases the requirement for ICS treatment and asthma severity increases the risk of an exacerbation. In our cohort, women with recurrent loss of control are probably similar to findings from previous studies [25] in that ICS use is a reflection of asthma severity, and therefore, they are more susceptible to worsening disease in pregnancy especially if there is a lack of compliance with medication. Previous work has demonstrated that cigarette use in pregnancy is associated with worsening asthma and an increased incidence of exacerbations [15], which may also apply to an increased risk of loss of control as demonstrated in this study.…”
Section: Discussionsupporting
confidence: 88%
“…Aside from all the problems associated with social disadvantage, the risks for a loss of control were age, BMI, cigarette use and ICS use, which are similar to previous studies examining risk factors associated with exacerbations [5]. A population-based study of 4434 asthmatic women examined ICS treatment pre-pregnancy and during pregnancy [25]. It was found that 50% of all women stopped or reduced their ICS intake with pregnancy and 8.2% exacerbated with cessation, while 20% of all other women exacerbated.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…The change in dispensed ICS prescriptions before, during and after pregnancy was reported from 12 databases (Table ) in eight publications . Two studies collected data on ICS use before, during and after pregnancy using comparable methods and therefore were pooled for analysis/reporting (data from eight European databases).…”
Section: Resultsmentioning
confidence: 99%
“…Of the six database studies that could not be included in the pooled analysis due to differences in data collection, two used the same Korean data set but examined different outcomes . The first, by Koo et al reporting on 115 169 pregnant women with asthma, assigned ranks to controller medication for asthma, with low ranks (“1” and “2”) for ICS only inhalers and low ICS dose combination inhalers, rank “3” for medium‐to‐high ICS dose combination inhalers and the highest rank “4” to OCS .…”
Section: Resultsmentioning
confidence: 99%